Automatic gas booking systemusing IoT - Chandan, M; Malladi, Srinivas; Nishitha, M; Sindhu Priya, K; Sree Lekha, Y (International Journal of Engineering and Technology, 2018)
Gas Booking is a major requirement in every individual life. The need of this project is to save time while booking the gas. When we call to the gas distributor our request may not be recorded or call may not be connected. These all waste the person’s time. If we haven’t noticed the completion of gas we need to book it in black for more money. By this project the level of gas will be monitored at all the time and we get message when gas is about to complete. In this paper we would like to advocate a micro-controller-based system in which a weight sensor, and load cell are used to discover the weight of the gas present within the cylinder. This unit is integrated into an alarm unit, to sound an alarm or supply a visual indication when the LPG is completed. The sensor has proper sensitivity and a brief reaction time at fewer prices. If gas completion is identified, message to the lawful candidate or family member the usage of cellular network known as GSM is dispatched routinely. It also gives the additional quality to calculate the weight of LPG cylinder and displays its value in Liquid Crystal Display (LCD). Amount of gas less than or equivalent to 10kg the cylinder is booked mechanically by sending textual content message to a provider. Additionally, when the cylinder has a weight of 0.5kg or less, it alerts the lawful candidate or family member by sending a notification to refill the cylinder.